KAJIAN BENTUK DAN FUNGSI SENI KERAJINAN LAKUER TEPAK SIRIH PALEMBANG - Husni Mubarat (Besaung : Jurnal Seni Desain dan Budaya, 2016)
Art Craft Lakuer Tepak Sirih Palembang, a cultural heritage of the past is handed down from generation to generation. The craft has a wide range of products that serve as a means of household fittings such as plates, tins, trays, betel slap and others. As for becoming the focal point of the author are Art Craft Lakuer Tepak Sirih Palembang. Historically craft Lakuer Palembang was originally brought by traders from the Chinese and India around the 6th century AD whose purpose is as a tribute or a prize given to the kings of Srivijaya, while traditions chewing or menginang in South Sumatra, especially in Palembang estimated in the 6th century until the 7th century AD this tradition influenced by Hindu-Buddhist culture which was followed by the Arabs. As artepak culture, the existence of such craft should be appreciated as works of art valued craft classic. The values contained in it is a reflection of the value of the historical, social, cultural and aesthetic. Visually, Art Craft Lakuer Tepak Sirih Palembang resemble the shape of truncated pyramid, with a slope of approximately 25 degrees, with a form of decoration in the form of animal motifs distilir and plants motif. Overall physical form (visual) this craft also emerged from the shades of color, such as dark golden brown, crimson red and golden yellow and combination black ink china. Each of these colors give shape (visual effects) with the uniqueness of each. In terms of functionality, this craft discount variety of functions, among which are a function of social, cultural and decorative objects (as works of craft art in terms of art crafts). Overall it can be said craft craft unique, different from the craft in most other areas, especially in Sumatra. In particular goal of this study is to know and understand the forms and functions that exist in the craft Lakuer Tepak betel Palembang. This study is expected to be the starting point for the author to learn more about the craft Lakuer Palembang in general, especially in this case are Art Craft Lakuer Tepak Sirih Palembang, either through research or in the form of product development as a work valuable cultural and economic value, thus. The results of this study are expected later can be beneficial as science, both for themselves writers, academics, artisans and community lakuer PalembangKeywords :Form, Function, Lakuer, Tepak Sirih Palembang